2013
DOI: 10.1115/1.4023652
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Flow Structures Associated With Low Aspect Ratio Elliptical Cavities

Abstract: The flow regimes associated with a 2:1 aspect ratio, elliptical planform cavity in a turbulent flat plate boundary layer have been systematically examined for various depth/width ratios (0.1 to 1.0) and yaw angles (0° to 90°), using a combination of wind tunnel experiments (involving Particle Image Velocimetry and helium bubble visualization) and Computational Fluid Dynamics (CFD) simulations (employing threedimensional steady calculations with the Reynolds Stress model turbulence closure).Satisfactory agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 75 publications
(157 reference statements)
0
5
0
Order By: Relevance
“…The value of C p,peak at x * = 0.92 is 0.28, which is slightly less than that for ε = 0. However, there is greater flow expansion near the rear edge because of an increase in the entrainment over the sidewall [15]. For L/H = 14.33, there is less expansion near the rear edge, and the value of C p,peak at x * ≈ 0.91 is 0.32.…”
Section: Mean Surface Distributionmentioning
confidence: 96%
See 2 more Smart Citations
“…The value of C p,peak at x * = 0.92 is 0.28, which is slightly less than that for ε = 0. However, there is greater flow expansion near the rear edge because of an increase in the entrainment over the sidewall [15]. For L/H = 14.33, there is less expansion near the rear edge, and the value of C p,peak at x * ≈ 0.91 is 0.32.…”
Section: Mean Surface Distributionmentioning
confidence: 96%
“…(𝒂) 𝜀 = 0 (𝒃) 𝜀 = 0.66 (𝒄) 𝜀 = 0.87 The region in which Cp is positive moves further upstream, and an arc-shaped pressure pattern is shown in Figure 6b,c for  = 0.66 and 0.87. Hering and Savory [15] demonstrated that there is an increase in entrainment over the sidewall for rectangular cavities with a greater value for L/W. For elliptical cavities, there is early shear layer impingement on the cavity floor as  increases.…”
Section: Global Pressure Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…3a that the vortex eye location is almost not shifting with mainstream Reynolds numbers, and to quantify it, an attempt has been made to extract the location of the vortex eye. The vortex eye in the recirculation zone in the cavity can be identified easily by the local pressure minima criterion [15]. Hence, in the present work, the local pressure minima criterion is used to determine the vortex eye location.…”
Section: Cavity Flow Structurementioning
confidence: 99%
“…(10) to measure the shear layer thickness as it is a measure of maximum shear [20]. In the present work, the shear layer growth along the axial directions is extracted using the widely used formula, vorticity thickness, d x [6,15,16,21] as given by,…”
Section: Shear Layer Growth Ratementioning
confidence: 99%